Nomogram model of functional outcome for endovascular treatment in patients with acute basilar artery occlusion - Li, Lei; Lv, Jin; Han, Jian-jia; Gao, Yuan; Yan, Zhao-xuan; Wu, Qi; Zhang, Xiao-li; Gao, Feng (Frontiers in Neurology, 2023)
The efficacy and safety of endovascular treatment (EVT) in acute basilar artery occlusion (ABAO) has been confirmed by four randomized clinical trials.Nevertheless, the predictors of a 90-day favorable outcome after EVT have not been elucidated.We attempted to establish a nomogram for the prediction of a 90-day favorable outcome in ABAO patients with EVT.Methods Clinical data of ABAO patients with EVT were obtained from two nationwide clinical trial registries in China. Factors associated with a 90-day favorable outcome were screened by multivariable step-wise regression on the basis of univariable analysis. A nomogram was established to predict 90-day favorable outcome after EVT.The proportion of ABAO patients with a favorable outcome was 41.53% (157/378).National Institutes of Health Stroke Scale (NIHSS) <20 (odds ratio [OR]: 8.330; P-value <0.0001), posterior circulation Alberta Stroke Program Early CT (pc-ASPECT) score ≥7 (OR: 1.948; P-value =0.0296), Pons-Midbrain Index (PMI) score <2 (OR: 2.108; P-value =0.0128), Posterior Circulation Collateral Score (PC-CS) ≥5 (OR: 3.288; P-value <0.0001), local anesthesia (OR: 0.389; P-value =0.0017), time from onset to recanalization (OTR ) <330 minutes (OR: 2.594; P-value =0.0013), and no occurrence of early neurological deterioration (END) (OR: 0.039; P-value <0.0001) were included into the nomogram, with C-index values of 0.8730 and 0.8857 in the training and the internal validation set, respectively. Conclusions The proposed nomogram provided a reliable prognostic scale, which can be employed in clinical settings for the selection and clinical management of ABAO patients. REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT03370939